2020
DOI: 10.1080/08998280.2020.1753455
|View full text |Cite
|
Sign up to set email alerts
|

Predictive value of lateral soft tissue thickness for complications after total hip arthroplasty with a lateral incision

Abstract: The purpose of this study was to determine the relationship between soft tissue thickness lateral to the greater trochanter, as measured on anteroposterior pelvis radiograph, and postoperative complications following primary total hip arthroplasty. A retrospective review of 1110 consecutive patients treated at a single institution from 2003 to 2011 was conducted. Postoperative complications were divided into surgical site infections, deep wound infections, noninfectious surgical complications, need for revisio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
15
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(17 citation statements)
references
References 30 publications
0
15
1
Order By: Relevance
“…When addressing total knee arthroplasty, while Watts at al 14 have found elevated SRM to be associated with increased risk for SSI, Gupta el al 25 have actually described higher SRM to be a protective factor. Likewise, following total hip arthroplasty, Sprowls et al 16 have found thick subcutaneous fat to be related with SSI, while Bell at al 17 did not reach similar results.…”
Section: Discussionmentioning
confidence: 91%
See 2 more Smart Citations
“…When addressing total knee arthroplasty, while Watts at al 14 have found elevated SRM to be associated with increased risk for SSI, Gupta el al 25 have actually described higher SRM to be a protective factor. Likewise, following total hip arthroplasty, Sprowls et al 16 have found thick subcutaneous fat to be related with SSI, while Bell at al 17 did not reach similar results.…”
Section: Discussionmentioning
confidence: 91%
“…10,11 Subcutaneous radiographic fat measurement (SRM) is an emerging tool for SSI risk prediction in the field of general surgery 12,13 and orthopedic surgery. [14][15][16][17] Due to the devastating consequences of SSI in the fragile FHF population, early identification of risk factors is of critical importance. In this study, we explore whether SRM is associated with increased risk for SSI following fragility hip fracture surgery.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The results of our study suggest an association between the SRM at the hip and the risk of APJI in patients after total hip replacement surgery. Sprowls et al (2020a) retrospectively reviewed 1110 patients, identifying increased lateral soft-tissue thickness and body mass index as factors associated with surgical site infection and deep infection and lateral soft-tissue thickness with revision surgery as well. A value > 5 cm was predictive of surgical site infection, deep infection, and revision surgery.…”
Section: Discussionmentioning
confidence: 99%
“…It does not take into consideration fat distribution or muscle composition 14,15 . Other specific quantification methods, such as percent body fat, have been shown to correlate more closely with perioperative risks after TJA but requires specialized testing that may not be readily available 16,17 .…”
mentioning
confidence: 99%